THE ROLE OF CREDIT MANAGEMENT ON FINANCIAL PERFORMANCE - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This section covers the background of the study, statement of the problem, purpose of the study, research objective, research questions, and the scope of the study and the significance of the study. In the whole world commercial bank is financial institution which accepts deposits, makes business loans, and offers related services (Fernando 2006). Commercial banks also allow for a variety of deposit accounts, such as checking, savings, and time deposit These institutions are run to make a profit and owned by a group of individuals, yet some may be members of the Federal Reserve System. While according to Home (2007) commercial banks offer services to individuals, they are primarily concerned with receiving deposits and lending to businesses